Designing, synthesis, and antimicrobial action of oxazoline and thiazoline derivatives of fatty acid esters. Issue 15 (18th November 2017) - Ahmad, Anis; Ahmad, Aiman; Sudhakar, Raja; Varshney, Himani; Subbarao, Naidu; Ansari, Saba; Rauf, Abdul; Khan, Asad U.
Abstract : In this study, a novel series of oxazoline and thiazoline were designed as inhibitors of cytochrome P450 14 alpha-sterol demethylase (CYP51) from Candida albicans and peptide deformylase (PDF) of Escherichia coli . The long chain dibromo derivative of fatty acid esters on reaction with urea and thiourea gave their corresponding oxazolines and thiazolines, respectively. All the compounds were characterized by their spectral data (IR, 1 H NMR, 13 C NMR and MS) and tested for antibacterial and antifungal activity by disk diffusion assay and minimum inhibitory concentration by the broth microdilution method against gram-positive and gram-negative strains of bacteria as well as fungus strains. The investigation into antimicrobial screening revealed that all the compounds were found to be potent antimicrobial agents. After calculating likeness drug properties of the compounds by Prediction of Activity Spectra for Substances software, ADMET-related descriptors were computed to predict the pharmacokinetic properties for the active and bioavailable compounds by discovery studio 2.5. Molecular docking studies have been performed on PDF of E. coli and CYP 450-14DM of C. albicans to understand the mode of binding of the molecules in the active site of the receptor. Compounds (2-amino-5-(carbomethoxyoctyl)-1, 3-oxazoline, 2-amino-5-(carbomethoxyoctyl)-1, 3-thiazoline and 2-amino-4-pentyl-5-[(8'R)-8' hydroxy (carbomethoxydecyl)-1, 3-oxazoline) showed excellent antimicrobial activity nearly equivalent to the control compounds and compounds, 2-amino-4-octyl-5-(carbomethoxyheptyl)-1, 3-oxazolin, 2-amino-4-(2'R)(2'-hydroxy octyl)-5-(carbomethoxyheptyl)-1, 3-oxazoline and 2-amino-4-pentyl-5-[(8'R)-8'-hydroxy(carbomethoxy decyl)-1, 3-oxazolineshowed vasodilation and antihypertensive properties. Furthermore, a computational analysis of physicochemical parameters revealed that the most of the compounds possessed drug-like attributes. Using Bioinformatics approach, we found a correlation between the observed and predicted antimicrobial activities. Abstract : A series of novel oxazoline and thiazoline derivatives of long chain unsaturated fatty acid esters were synthesized from urea and thiourea, respectively, and screened for their antibacterial activity against Escherichia coli, Methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pyogenes, Klebsiella pneumonia and antifungal activity against Candida albicans, Aspergillus fumigatus, Penicillium marneffei, Trichophyton mentagrophytes .